Validity and reliability of the Turkish version of caregiver self-assessment questionnaire. Issue 22 (22nd October 2020) - Aşkın, Ayhan; Atar, Emel; Şengül, İlker; Tosun, Aliye; Demirdal, Ümit; Elmalı, Ferhan
Abstract: Objective: This study aims to translate the Caregiver Self-Assessment Questionnaire (CSAQ) into Turkish language and to test its reliability and validity in Turkish informal family caregivers. Materials and methods: This is a cross-sectional and methodological study. Eighty family caregivers (54.53 ± 12.07 years; range 25 to 77 years; 65 females, 15 males) were included in the study. Demographic properties of the participants (age, sex, education, occupation, marital status), relationship with care recipient, caregiving time, main diseases of the patients were recorded. After that CSAQ, Caregiver Well-Being Scale (CWBS) and Hospital Anxiety Depression Scale (HADS) were used for data collection. A test-retest interval of seven-days was used to assess the reliability. Internal consistency between the items was assessed by Cronbach's alpha coefficient. For reliability; test-retest reliability, intraclass correlation coefficient, and paired sample t tests were used. Intercorrelation of variables was performed with Spearman's rho tests. A ROC curve and sensitivity and specificity analysis were performed to determine the ability of the CSAQ to predict depression or anxiety. Results: Totally 80 participants completed test/retest procedures. Content Validity Index values of the Items were sufficient and all items were included in the questionnaire. During exploratory factor analysis, 1 factor with eigenvalues greater than 1 were extracted, explaining 62.36% of the total variance. The corrected item total correlation coefficients for Item 2 and Item 5 were found to be <0.3. Therefore, these two items were omitted. Cronbach's α value was found as 0.90 (excellent level). Test-retest reliability (Intraclass correlation coefficient values range: 0.93-0.97) of the CSAQ was found to be excellent. Statistically negative moderate correlations were detected between CSAQ total score and CWBA basic needs and activities of living sub scores ( rho  = −0.605, rho  = −0.523, p  < 0.001), while positive strong correlations were detected between HADS depression and anxiety scores ( rho  = 0.610, rho  = 0.651, p  < 0.001). CSAQ score of 9 or greater resulted in a sensitivity of 0.56 and a specificity of 0.87 for depression and sensitivity of 0.84 and a specificity of 0.83 for anxiety. According to the scoring instructions of CSAQ with the positivity of any one of four criteria, we found sensitivity of 0.87 for depression and 0.96 for anxiety. Conclusion: The Turkish version of the CSAQ is a valid and reliable questionnaire for evaluating stress-levels of informal family caregivers. Implications for rehabilitation: Measures of caregivers' psychological status are of clinical value. The Caregiver Self-Assessment Questionnaire functions as a screening measure for symptoms of depression and anxiety. The Turkish version of the Caregiver Self-Assessment Questionnaire is a valid and reliable questionnaire for evaluating stress-levels of informal family caregivers.